La novellisation dans le réseau intermédiatique du Petit Nicolas - Benoît Glaude (Belphégor)
The intermedial network of Little Nicholas is not limited to Jean-Jacques Sempé’s and René Goscinny’s illustrated short stories (1959-1965), which have become classics of children’s literature. Before that, they were born in cartoons and comics, and they have been brought to the big and small screen ever since, including an animated TV series, which is being novelized. This paper proposes a reading of some Little Nicholas’ short stories as direct novelizations – and some novels based on animated cartoons, as indirect novelizations – of the comics pages published in 1955-1956. Novelization will be considered both as a cultural practice and as a creative process.